10 years of success achieved by eribulin while treating HER2-negative mBC: from randomized studies to routine practice - I. V. Kolyadina (Опухоли женской репродуктивной системы, 2021)
The article reviews studies evaluating the efficacy and safety of eribulin chemotherapy in patients with HER2-negative advanced breast cancer. It analyzes the results derived from large randomized studies, highlights the main advantages peculiar to eribulin, and describes the key mechanisms of the antitumor activity displayed by the drug. Among those presented, there are significant retrospective studies evaluating the role of eribulin chemotherapy in late and early advanced breast cancer treatment lines, as well as an analysis of surveys aimed to evaluate the efficacy of the drug in various clinical settings (for visceral metastases, brain lesion, and in elderly patients). This article reflects the main results of Russian population analyses evaluating the efficacy and safety of eribulin chemotherapy in routine clinical practice.